Modified woodflour as thermoset fillers Part I. Effect of the chemical modification and percentage of filler on the mechanical properties - Marcovich, Norma Esther (2001)
Composites made from an unsaturated polyester/styrene thermoset matrix and esterified woodflour have been prepared and tested. Different degrees of esterification of the wood particles with maleic anhydride were obtained by using different times of reaction, which lead to materials with varied final properties. Water absorption performed on treated particles indicates that they are more hydrophobic than the untreated ones. Flexural, compression and dynamic-mechanical tests were performed on composites to find out an optimum level of chemical modification of the woodflour. Moreover, the relationship between the filler content and the composite final properties was also studied for a selected filler treatment. An important increment in particle dispersion was obtained by modifying the woodflour with maleic anhydride.